Examination and Research on the Epitaph of Yang, the Late Wei Dynasty’s General of Pacifying Remote Areas and Governor of Huazhou - Liu, Zheng (Technium Social Sciences Journal, 2026)
The Epitaph of Yang Shu, Late Wei Dynasty Zhenyuan General and Governor of Huazhou, is a valuable historical text that not only describes his native place and family background but is full of information regarding his life experience and death. There are no historical mentions of Yang Shu in historical literature until now but is mentioned in some historical contexts in a sparse format. The epitaph of Yang Shu can therefore fill a gap in historical literature to a certain extent. The epitaph of Yang Shu has contributed to a certain extent to clarifying some facts related to Yang Shu in historical literature regarding its dates of birth and death and official and familial history. The epitaph can therefore provide important text for academic study related to the Hongnong Yang clan. The historic merits of Yang Shu to a certain extent can denote that for prominent families and dynasties like that in the North Wei Dynasty, especially in relation to growing their members in a superior fashion.